Markets in motion : (John Wiley, 2005)
Markets in Motion is a graphical overview of the economic conditions and events that have influenced the U.S. stock market since 1900. Decade by decade, you'll examine how different economic and policitcal environments can be directly correlated to stock market movements. Each decade features graphs displaying the performance of the Dow Jones Average, the Dow Jones price to dividend ratio, industrial production, money supply, consumer price index, T bill rate, and the Discount rate. Embedded on the graphs are short descriptions of important political, economic, and historical events. Use this information to reference similar environments today and gain an edge in determining the future direction of the market